Extensive alternative polyadenylation during zebrafish development - Ulitsky, Igor; Shkumatava, Alena; Jan, Calvin H.; Subtelny, Alexander O.; Koppstein, David; Bell, George W.; Sive, Hazel; Bartel, David P. (Genome Research, 2012)
The post-transcriptional fate of messenger RNAs (mRNAs) is largely dictated by their 3′ untranslated regions (3′ UTRs), which are defined by cleavage and polyadenylation (CPA) of pre-mRNAs. We used poly(A)-position profiling by sequencing (3P-seq) to map poly(A) sites at eight developmental stages and tissues in the zebrafish. Analysis of over 60 million 3P-seq reads substantially increased and improved existing 3′ UTR annotations, resulting in confidently identified 3′ UTRs for >79% of the annotated protein-coding genes in zebrafish. mRNAs from most zebrafish genes undergo alternative CPA, with those from more than a thousand genes using different dominant 3′ UTRs at different stages. These included one of the poly(A) polymerase genes, for which alternative CPA reinforces its repression in the ovary. 3′ UTRs tend to be shortest in the ovaries and longest in the brain. Isoforms with some of the shortest 3′ UTRs are highly expressed in the ovary, yet absent in the maternally contributed RNAs of the embryo, perhaps because their 3′ UTRs are too short to accommodate a uridine-rich motif required for stability of the maternal mRNA. At 2 h post-fertilization, thousands of unique poly(A) sites appear at locations lacking a typical polyadenylation signal, which suggests a wave of widespread cytoplasmic polyadenylation of mRNA degradation intermediates. Our insights into the identities, formation, and evolution of zebrafish 3′ UTRs provide a resource for studying gene regulation during vertebrate development.
10.1101/gr.139733.112